PATIENT TRUST THROUGH THE ROLE OF MEDICAL STAFF OF GOVERNMENT-OWNED REGIONAL GENERAL HOSPITALS - Hadiyati Hadiyati; Bambang Suroto; Eddy Jusuf (Faculty of Economics and Business, University of Pasundan, 2019)
Government-owned regional general hospitals are not the only hospitals in a region. Competition with private and foreign hospitals requires government-owned hospitals toimprove. The question is whether the role of medical staff is able to increase patient satisfaction and trust. This quantitative research was conducted in M. Sani Regional General Hospital in Tanjung Balai Karimun Regency, Riau Islands Province. The data were collected using questionnaires from 100 patients or families of inpatients totaling and taken using accidental sampling. The data were analyzed quantitatively using SEM analysis tools. The results showed that the variables of responsiveness and motivation given by the medical staff to patients had a significant and positive influence on patient satisfaction and had an impact on patient trust in the services provided by the hospital.